Precrastination and the cognitive-load-reduction (CLEAR) hypothesis. Issue 1 (2nd January 2020) - Patterson, Emma E.; Kahan, Todd A.
ABSTRACT: Precrastination is the tendency many individuals have to complete a task as soon as possible in order to get it out of the way [Rosenbaum, D. A., Gong, L., & Potts, C. A. (2014). Pre-crastination: Hastening subgoal completion at the expense of extra physical effort. Psychological Science, 25 (7), 1487–1496. doi:10.1177/0956797614532657 ]. The current study ( N = 48) examined whether precrastination is affected by a concurrent memory load as predicted by the cognitive-load-reduction (CLEAR) hypothesis. Participants completed a bucket-carrying task under different memory-load conditions. In addition, the amount of physical effort was manipulated by changing the distance people needed to walk while carrying the weighted buckets. The tendency to precrastinate by picking up a near bucket and carrying it further than necessary was affected by the memory load. People were more likely to precrastinate when doing so resulted in the more rapid renewal of cognitive resources and were less likely to precrastinate when this required that the memory load be held for a longer period of time. These data are consistent with the position that precrastination is linked with working memory resources and occurs in an attempt to clear items from a mental to-do list.